Use of the CO2 laser on orthodontic patients suffering from gingival hyperplasia - Sabrina Kívia Gama (2007)
Objective: The present study aimed to assess the effect of the use of the CO2 laser on the treatment of gingival hyperplasia in orthodontic patients wearing fixed appliances. Background Data: Gingival hyperplasia is a condition very frequent in patients undergoing fixed orthodontic treatment. Amongst the treatments available for this is the use of surgical lasers. Methods: Ten patients entered this study and signed an informed consent. Seventy-five anterior teeth with gingival hyperplasia were selected for laser surgery. Prior to surgery, the length of the crowns were measured using a digital caliper, and depth of the pocket was probed. The hyperplasic gingival was removed with a CO2 laser under local anesthesia. Immediately after surgery, measurement of the length of the crowns and probing were carried out and were repeated. Results: The results were statistically analyzed and significant differences were detected regarding the length of the crown (p = 0.000) and depth of the gingival sulcus (p = 0.000). Conclusion: It is concluded that the use of the CO2 laser was effective in the treatment of gingival hyperplasia. (c) Mary Ann Liebert, Inc.